Similarities in lindane induced alterations in protein expression profiling in different brain regions with neurodegenerative diseases. Issue 22 (13th October 2015) - Mudawal, Anubha; Singh, Anshuman; Yadav, Sanjay; Mishra, Manisha; Singh, Pradhyumna Kumar; Chandravanshi, Lalit Pratap; Mishra, Juhi; Khanna, Vinay K.; Bandyopadhyay, Sanghamitra; Parmar, Devendra
Abstract : Previous studies have reported that lindane, an organochlorine pesticide induces oxidative stress in rat brain that may lead to neurodegeneration. However, as the proteins involved in lindane induced neurodegeneration are yet to be identified, the present study aims to identify the proteins that may regulate lindane induced neurotoxicity. The data showed that repeated exposure of lindane (2.5 mg/kg) for 21 days to adult rats significantly increased the reactive oxygen species and lipid peroxidation in different brain regions. Proteomic study revealed that lindane induces major dysregulation in the ubiquitin proteasome pathway. Alterations in the expression of molecular chaperones in brain regions and an increase in the expression of α‐synuclein in substantia‐nigra and corpus‐striatum and amyloid precursor protein in hippocampus and frontal‐cortex suggests the accumulation of proteins in these brain regions. Western blotting also revealed alterations in the dopaminergic and cholinergic pathways in hippocampus and substantia‐nigra isolated from lindane treated rats. Neurobehavioural data indicating alterations in learning and working memory, conditioned avoidance response and motor function, supports the proteomic data. The data suggest that repeated exposure of lindane to adult rats induces alterations, which are similar to that seen in neurodegenerative diseases.